The Effect of Land and Building Acquisition Tax (BPHTB), Land and Building Tax, Restaurant Tax, Parking Tax and Street Lighting Tax on Regional Original Income in Surakarta Residency Government 2017-2023 - Raisa Tanjung Sari, Della; Putri, Eskasari (Journal of Accounting and Finance Management, 2025)
This study aims to empirically analyze the effect of Land and Building Acquisition Fee (BPHTB), Land and Building Tax, Restaurant Tax, Parking Tax, and Street Lighting Tax on Local Original Income. This study was conducted at the Regency/City Governments in the former Surakarta Residency for the 2017-2023 Fiscal Year. The study used a quantitative research approach to collect and analyze data. The population in this study were all district/city governments in the former Surakarta Residency for the 2017-2023 fiscal year consisting of 6 regencies and 1 city. The sampling method used was purposive sampling, with a total sample of 41 data. The analysis used was multiple linear regression and descriptive statistics. The results of the data analysis showed that the variables of Land and Building Acquisition Fee (BPHTB) and Land and Building Tax had an effect on Local Original Income. Meanwhile, the variables of Restaurant Tax, Parking Tax, and Street Lighting Tax had no effect on Local Original Income. This study expands the literature on the contribution of local taxes to local original income. This study provides a deeper understanding of the relationship between regional taxes and local revenue for district and city governments in Surakarta Residency from the 2017 to 2023 fiscal years.